Donor disc attachment assessment with intraoperative spectral optical coherence tomography during descemet stripping automated endothelial keratoplasty - Wylegala, Edward (Medknow Publications & Media Pvt Ltd, 2013)
Optical coherence tomography has already been proven to be useful for pre- and post-surgical anterior eye segment assessment, especially in lamellar keratoplasty procedures. There is no evidence for intraoperative usefulness of optical coherence tomography (OCT). We present a case report of the intraoperative donor disc attachment assessment with spectral-domain optical coherence tomography in case of Descemet stripping automated endothelial keratoplasty (DSAEK) surgery combined with corneal incisions. The effectiveness of the performed corneal stab incisions was visualized directly by OCT scan analysis. OCT assisted DSAEK allows the assessment of the accuracy of the Descemet stripping and donor disc attachment.